An electrically controlled light-scattering device based on liquid crystal/polymer microsphere composites. Issue 5 (8th April 2020) - Li, Xiaoshuai; Guo, Yuqiang; Huai, He; Yang, Yanling; Sun, Yan; Zhang, Chi; Sun, Yubao
ABSTRACT: There is a widely applied prospect of electrical controlled liquid crystal (LC) light-scattering device. Numerous electrical controlled LC light-scattering technologies have been studied, but each technology has its own shortcomings, such as high driving voltage, high hysteresis, complex electrode structure, and serious heating. In this work, the composite of LC and polymer microspheres are used to fabricate light-scattering devices. This device is operated by the vertical electric field and does not require complex preparation process. LC/polymer microsphere composite has the advantages of low driving voltage and zero hysteresis. The role of microspheres in the composites is to change the size and density of a refractive-index-mismatched micro-domain. The effects of the ratio, particle size, and refractive index of microspheres on the optical characteristics of a composite are studied. The normal directional light transmittance at the transparent state and light-scattering state decreases with an increasing weight ratio of microspheres. The particle size of microspheres has negligible influence on the electro-optical properties of composites when the weight ratio of microspheres is small. The LCs doped with Polymethylsilsesquioxane (PMSQ) microspheres or polymethyl methacrylate (PMMA) microspheres are compared, and the mismatched refractive index and density of micro-domain show the influence on the electro-optical properties of the composites. Graphical abstract: